Pengaruh Konsentrasi Dan Rasio Berat Graphene Nanosheets (GNSS) Terhadap Karakteristik Hot Rolled Sheet (HRS) - Bahri, Ahmad Syaiful; Amri, Amun; Shalahuddin, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Hot rolled sheet (HRS) characteristics can be improved by adding additives in the asphalt. This study aims to analyze and determine the effects of concentration and weight ratio of graphene nanosheets (GNSs) additive on the characteristics of HRS. The research was carried out in several stages, starting from the preparation of graphite powder from 2B pencils, preparation of 60/70 penetration asphalt and aggregates, making GNSs solution using the turbulance assisted shear exfoliation (TASE) method and continued with the manufacture of HRS with variations in GNSs concentrations of 10 mg/ml, 20 mg/ml and GNSs weight ratios of 0%, 5%, 10%, 15%. The results showed that the concentration and weight ratio of GNSS could affect the stability value, flow and marshall quotient (MQ) of the HRS. The best results were obtained at a concentration of 20 mg/ml and a weight ratio of 15% GNSs, with a stability value of 1541.19 kg, flow of 4.13 mm and MQ of 391.74 kg/mm.Keywords : Asphalt, Graphene nanosheets (GNSs), Hot rolled sheet (HRS)